The Sustainability of Agro-Food and Natural Resource Systems in the Mediterranean Basin - Vastola, Antonella (Springer International Publishing : Imprint: Springer, 2015)
This book is focused on the challenges to implement sustainability in diverse contexts such as agribusiness, natural resource systems and new technologies. The experiences made by the researchers of the School of Agricultural, Forestry, Food and Environmental Science (SAFE) of the University of Basilicata offer a wide and multidisciplinary approach to the identification and testing of different solutions tailored to the economic, social and environmental characteristics of the region and the surrounding areas. Basilicata's productive system is mainly based on activities related to the agricultural sector and exploitation of natural resources but it has seen, in recent years, an industrial development driven by the discovery of oil fields. SAFE research took up the challenge posed by market competition to create value through the sustainable use of renewable and non-renewable resources of the territory. Moreover, due to its unique geographical position in the middle of the Mediterranean basin, Basilicata is an excellent "open sky" laboratory for testing sustainable solutions adaptable to other Mediterranean areas. This collection of multidisciplinary case studies and research experiences from SAFE researchers and their scientific partners is a stimulating contribution to the debate on the development of sustainable techniques, methods and applications for the Mediterranean regions.